2022
DOI: 10.1007/s00607-022-01112-2
|View full text |Cite
|
Sign up to set email alerts
|

Passive social sensing with smartphones: a systematic review

Abstract: Smartphones are widely used hubs of personal communication. With their many sensors, they are capable of monitoring social behaviours. Calls, messages, application usage and even face-to-face conversations can be captured by smartphones. These data are then used to study psychological, behavioural and clinical issues, thus providing an objective and continuous perspective on people’s social lives. However, compared with questionnaires, researchers are unfamiliar with the potential and challenges of smartphone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…GPS and Bluetooth are sensors that can be easily switched off from a smartphone’s main setting page and may be seen as more intrusive forms of monitoring. This was supported by the finding that 35% of those interviewed felt “monitored” by the apps and the recurrence of “privacy” as a theme in RMT research for health care [ 38 ].…”
Section: Discussionmentioning
confidence: 87%
“…GPS and Bluetooth are sensors that can be easily switched off from a smartphone’s main setting page and may be seen as more intrusive forms of monitoring. This was supported by the finding that 35% of those interviewed felt “monitored” by the apps and the recurrence of “privacy” as a theme in RMT research for health care [ 38 ].…”
Section: Discussionmentioning
confidence: 87%
“…This fact may explain the high rates of missing data for passive monitoring found in the YouXin study [ 54 ], and in other passive monitoring studies [ 53 , 55 , 56 ]. In addition, participants mentioned power consumption was higher than before using the app, which is likely caused by passive monitoring [ 57 ]. Therefore, optimising passive data collection strategies to reduce missing data and power consumption is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Timestamped output from passive sensors also allows researchers to examine children’s digital behaviors at any time of day or night. However, Zhang et al (2022) found that only 10 out of 47 eligible studies considered ethical questions of informed consent when collecting passive sensing data from users’ smartphones (calls, messages, application usage). In their study of smart-home technology, Nelson and Allen (2018) highlight the researchers’ challenge of adapting not only to technological affordances but also to rapidly evolving public perceptions on permissible data practices.…”
Section: Non-participatory Methodsmentioning
confidence: 99%
“…In their study of smart-home technology, Nelson and Allen (2018) highlight the researchers’ challenge of adapting not only to technological affordances but also to rapidly evolving public perceptions on permissible data practices. Zhang et al (2022) recommend as ethical practice that the permissions granted to individual commercial applications should be strictly limited, telephone numbers should be encrypted, and Bluetooth/Wi-Fi MAC addresses and call/messages numbers anonymized, so that the data can ‘maintain uniqueness but lose traceability’ (p. 9). We concur with Zhang et al’s (2022) recommendation: a considerable number of American citizens experience a prevailing sense of resignation regarding the utilization of their data traces by corporations and marketers.…”
Section: Non-participatory Methodsmentioning
confidence: 99%
See 1 more Smart Citation